State of Entrepreneurship Attitude and Intention among Malaysian Youngsters - Hasliza Hassan; Abu Bakar Sade; Melissa Wendy Migin (International Journal of Family Business Practices, 2020)
Entrepreneurship among the youngsters in Malaysia is expected to spice-up the existing socio-economic development momentum. Many initiatives have been introduced to spur the entrepreneurship spirit among the youngsters. This research focuses on the attitude and intention of the youngsters in becoming entrepreneurs. A cross-sectional research was conducted to determine the attitude and intention of the youngsters to be an entrepreneur using a survey questionnaire. Descriptive and correlation analyses were conducted using 425 data that were collected from students who have taken the entrepreneurship course at the Multimedia University, Cyberjaya, Selangor, Malaysia. It is found that the youngsters have a positive attitude and intention towards entrepreneurship. Further findings also highlight that the positive attitude influences the positive intention for the youngsters to venture into entrepreneurship. Shaping the attitude and intention through the basic entrepreneurship knowledge that can be learned from formal education is expected to become an entrepreneurial engine to drive the economic development for the nation.